Effects on power, strength and lean body mass of menstrual/oral contraceptive cycle based resistance training - Wikström-Frisén, L.; Boraxbekk, C. J.; Henrikkson-Larsén, K. (The Journal of Sports Medicine and Physical Fitness, 2017)
BACKGROUND: The purpose of this study was to investigate the effects of menstrual and oral contraceptive cycle on a high frequency periodized leg resistance training in trained women. METHODS: Two groups performed high frequency leg resistance training for two weeks of each menstrual/oral contraceptive cycle for four months. The remaining part of the cycle they performed the leg training once a week. Group 1 (N.=19) trained with high frequency (5 times·w-1) during the first two weeks of each cycle, and group 2 (N.=19) during the last two weeks of each cycle. A control group (N.=21) performed regurlar (3 times·w-1) leg resistance training for four months. RESULTS: Significant increase in squat and countermovement jump, and peak torque values in hamstrings for group 1 were observed, but not in group 2. In the control group an increase in squat and countermovement jump, and peak torque (only left hamstring) was also observed. There was also a significant increase in lean body mass of the legs in group 1 only. There were no evident differences in the training effects between women with or without oral contraceptive. CONCLUSIONS: The high frequency periodized leg resistance training during the first two weeks of the menstrual cycle is more beneficial to optimize training than in the last two weeks. Resistance training during the first two weeks of the menstrual cycle even resulted in a larger gain of lean body mass than regular training.